2016 Lao PDR Enterprise Survey : Country Highlights - World Bank Group (World Bank, Washington, DC, 2017)
The World Bank Group conducted face-to-face interviews with top managers and business owners of 368 enterprises in Lao PDR from January 2016 through June 2016. The Enterprise Survey (ES) sample is representative of Lao PDR’s formal private sector. The ES covers several aspects of business environment along with measures of firm performance. The main highlights from the survey are: firms in Lao PDR lag behind comparator countries in terms of annual sales and employment growth; fewer firms use bank financing than in 2012, but the proportion of bank-financed investments has increased; compared to 2012, Laotian firms spend less time to obtain permits and to comply with regulations; fewer firms in Lao PDR are offering formal training compared to 2012 and to regional comparators; and firms consider informal competitors as the biggest business environment obstacle.